Anticompetitive behaviour in the audit services market by the Big audit firms: Evidence over time - Singh, Harj (Virtus interpress, 2013)
This study investigates the existence of anticompetitive behaviour and cartel pricing by the Big4 international providers of auditing services (resulting from the halving in the number of such providers from the Big8 to Big4).This study uses both a composite and dis-aggregated measure for auditor attributes (namely, auditor reputation, industry specialisation, provision of non-audit services and auditor tenure) and regresses the derived measure against changes in audit fees for the periods 2001 to 2003, 2003 to 2005 and 2001 to 2005 for a total sample of 600 firm-year observations.Main results from longitudinal multivariate analysis indicate that there is no significant association between the four auditor attributes utilised in this study with changes in audit fees over the observation window. This study finds no evidence of anti-competitive behaviour and cartel pricing by Big4 auditors resulting from increased audit market concentration. This has implications in relation to the need to consider legislation to reduce the power and influence of the Big4 audit firms and this subsequently has flow-on implications for the management of firms.